Studi Kritis Sinkritisme Iman Kristen Suku Ono Niha Di Gereja Beth-El Tabernakel Kristus Alfa Omega Afulu - Zalikhu, Itoloni; Gidion, Gidion; Astuti, Tri (JOURNAL of THEOLOGICAL STUDENTS, 2025)
This study critically examines the syncretism of the Christian faith among the Ono Niha Tribe in GBT KAO Afulu, particularly regarding the belief in ancestral spirits (Malaika Zinomate). Using a qualitative method involving interviews with church and community leaders, along with literature and biblical studies, the research reveals a blend of Christian teachings with local traditions that conflict with biblical doctrine. Practices such as death rituals and prayers to ancestors hinder the congregation’s spiritual growth and obscure core Christian teachings. The study affirms the biblical truth that there is no communication between the living and the dead and highlights the need for teaching grounded in Scripture. It recommends a contextual approach that filters, rather than rejects, local culture through the lens of the Gospel, alongside holistic evangelism and biblical instruction to overcome syncretism and foster true spiritual transformation. Key Word: Syncretism, Christian Faith, Ono Niha Tribe, Spirits of the Dead